RADIO LABELING OF BANANA GRAPHS - Sarbaini, Sarbaini; Nazaruddin, Nazaruddin; Rizki, Muhammad; Umam, Muhammad Isnaini Hadiyul; Hamzah, Muhammad Luthfi; Prasetyo, Tegar Arifin (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Let G=(V, E) be a graph. An L(3,2,1) labeling of G is a function such that for every , , and if . Let , a labeling is a labeling where all labels are not greater than . An ) number of , denoted by , is the smallest non-negative integer such that has a labeling. In this paper, we determine of banana graphs.